Tersedianya Potensi Suplai Dan Drainasi Persawahan Danda Besar Melalui Revitalisasi Prasarana Hidraulik Tingkat Tersier - Triadi, L Budi; Simanungkalit, Parlinggoman; Fernandus, Maruddin (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2010)
The low agriculture productivity at Danda Besar tidal swamp area is related with the existing water management system which is still at macro and meso level, and not fulfilling the paddy field water supply (micro water management system). Planting is carried out only in the wet season because the insufficient water management system does not provide available water supply in dry season. Impact of this problem include among others that the canal system become shallow and covered by vegetation. Quaternary canals are also not available. The selected location of this study is the Tertiary T2 Kanan Canal at Danda Jaya, a village in Kabupaten Barito Kuala, South Kalimantan province. These problems can be solved by water management revitalization and micro water management application equipped with a water regulator such as the Flap Gate. This study carrying out a 1 D hydraulic numeric simulation model in five scenarios by application of the DUFLOW computer program showed the improvement of canal capacity until adequate water is supplied during neap and spring tide. Thus, farmers can carry out a planting pattern twice a year in order to increase the crop production index from 100% to 150 – 200%.Keywords: Micro water management, flap gate, hydraulic numerical model